A randomised, controlled trial of a 4% cutaneous emulsion of sodium cromoglicate in treatment of atopic dermatitis in children. (June 2015) - Berth-Jones, John; Pollock, Ian; Hearn, Ross M. R.; Lewis-Jones, Sue; Goodfield, Mark; Griffiths, Christopher E. M.; Gulati, Ram; McHenry, Pamela; Abdullah, Anthony; Ott, Jennifer; Wright, Andrew; Walker, Benjamin; et al.
ABSTRACT Introduction: Atopic dermatitis (AD) is a chronic inflammatory skin disease. Sodium cromoglicate (SCG) is a chromone with anti-inflammatory, anti-itch and anti-allergic activity. This trial is a 12-week comparison (RCT) of a 4% SCG cutaneous emulsion with its vehicle in AD. Materials and methods: 208 children aged 2–12 years participated, 104 in each group. The primary endpoint was change in SCORAD score. Secondary endpoints included SASSAD score, topical steroid usage and global assessments. Results: SCORAD was reduced by 28% (SCG group) and by 19% (vehicle): difference was statistically significant (p = 0.03) after 8 weeks and nearly significant (p = 0.09) after 12. A similar result occurred in SASSAD (p = 0.001 at 8 weeks). In subjects without major protocol deviations (SCG-64, vehicle-63), difference in SCORAD remained significant at 12 weeks (p = 0.04). Weight of topical steroids reduced in both groups: −0.60 ± 1.3 g/day (35%), SCG and −0.05 ± 1.1 g/day vehicle (p = 0.04). Treatment success, defined as investigator global opinion graded very or moderately effective, was significantly more frequent in SCG group (p = 0.025). Application site discomfort reported by 12.5% of subjects in SCG group and 16.5% in vehicle group. Conclusions: SCG 4% cutaneous emulsion provides an effective, well-tolerated, steroid-sparing treatment for AD in children.